(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Nacua AE, Pacis HJM, Manalo JR, Soriano CJM, Tosoc NRN, Padirogao R, Clemente KJE, Deocaris CC. 2018. Macrofungal diversity in Mt. Makiling Forest Reserve, Laguna, Philippines: with floristic update on roadside samples in Makiling Botanic Gardens (MBG). Biodiversitas 19: 1579-1585. The Mt. Makiling Forest Reserve (MMFR) stands as a highly biodiverse habitat and the only intact natural forest near Metro Manila, the Philippines. It is one of the 18 key centers of plant biodiversity and 32 key ecotourism sites in the Philippines. In monitoring the implementation plans for protecting MMFR, the information pertaining to the mushroom biodiversity across decades is important. Therefore, we aim to study mushroom as an indicator for biodiversity since there has been studies in the past 30 years on the macrofungi of MMFR which we summarized here along with ours. Sampling was done in August 2017 based on the transect line of 1000 m along roadsides of Makiling Botanic Gardens (MBG). The distribution of the sampling units was carried-out using random and stratified sampling. Our study describes 21 macrofungal taxa collected from MMFR. Of these, 20 taxa belong to Basidiomycota and only one belongs to Ascomycota. Polyporaceae was found as the most dominant macrofungi family (24%). There were six (6) species that are medicinal, and no poisonous species noted. There are eleven (11) species in this study which are unique records compared with previous studies done in the macrofungi of MMFR. This is the first study done comparing mushroom across 30 years on a reserved area. Information on these macrofungal flora across time serves as a reference for the currently existing conservation efforts and implementation of biodiversity-related policies in MMFR.